The Type Of Code Mixing Used By The Indonesian Casters In A Match Of Pmpl South East Asia Championship Play-In Spring 2022 - Krisna, I Komang Krisna Armanda Putra; Putra, I Gede Agoes Caskara Surya (Journal of Language and Applied Linguistics, 2025)
Code Mixing is a combination of one language or more language from the speaker in communication. The phenomenon that I often encounter around me is that many young people use one or two languages in their spoken language. It is chosen because code mixing is very important for everyone, especially for people who live in bilingual or multilingual society. This study focuses on analyzing types of code mixing in Indonesian Casters of PMPL South East Asia Championship Play-In Spring 2022. The author used observation method in collecting the data by observe the video source , taking noted the code mixing utterances and classified it into table of data. This research used theory proposed by Hoffman (1991) to analyze the data. There are three types of code mixing based on syntactical patterns, they are : Intra-sentential code mixing, Intra-lexical code mixing, Involving a change of pronunciation. The result of this research is the dominant type found is Instra-sentential code mixing with 82 data from 114 total data. And the second is Intra-lexical with 32 data and the last is involving a change of prononciation with 0 data